ChemInform Abstract: Carpedilactones A—D, Four New Isomeric Sesquiterpene Lactone Dimers with Potent Cytotoxicity from Carpesium faberi. Issue 7 (29th January 2015) - Yang, Yong‐Xun; Shan, Lei; Liu, Qing‐Xin; Shen, Yun‐Heng; Zhang, Jian‐Ping; Ye, Ji; Xu, Xi‐Ke; Li, Hui‐Liang; Zhang, Wei‐Dong
Abstract Four new isomeric sesquiterpene lactone dimers, carpedilactones A (I), B (II), C (III), and D (IV) are isolated.